Do Memorial ao Uberlândia Clube: deslocamentos urbanos e temporais - Carbonel, Dino Giovanni Gozzer (2009)
Do Memorial ao Uberlândia Clube deslocamentos urbanos e temporais purposes the study of Memorial, artwork produced by Caetano de Almeida, within Arte na Cidade s Project. This event took place at Uberlândia in 1995, it was promoted and carried out by Department of Visual Arts of this University. Town Hall s Department of Culture was also a colaborator. The theme discussed was the city , as well as questions concerned with installations at urban space, since the artworks produced during the event would have automatically passed to configure a public collection. The present research aims to understand, through Memorial, Caetano de Almeida s manner of interpreting and recreating certain urban spaces of Uberlândia; it also aims to perceive the echo of Almeida s artistical praxis, inside the local imaginary of the town. We have tackled the problem related to the socialization of cultural elements within the complexity of time and space at Uberlândia. For realizing this, we ve done a kind of metodological mixing among Cultural History, Theory and Art History, Antropology and Urbanism. This research had its basis on thoughts of Roger Chartier, Paul Ricoeur, Peter Burke, Pierre Bourdieu, Jean Paul Fitoussi, Pierre Rosanvallon, Jesús Martín Barbero, and others. Gilberto Velho, Marc Augé and Michel de Certeau have helped us about individual actions at the contemporary society. Artistic aspects in the city have been tackled by thoughts of Giulio Carlo Argan, Nelson Brissac Peixoto and Tadeu Chiarelli. Finally, our analysis of Memorial were guided by reflections of Umberto Eco, Roland Barthes and Michel Foucault.